25 Current health-related quality of life in older adults with chronic ankle instability. (12th October 2015) - Simon, JE; Docherty, CL
Abstract : Background: Research regarding the current health-related quality of life (HRQoL) in individuals with chronic ankle instability (CAI) is limited; particularly in older adults. Individuals with CAI have reported decreased global and regional function; however, more research is required to determine the extent to which CAI influences HRQoL. Objective: To determine whether HRQoL and region specific outcomes differ between older adults with and without CAI. Design: Case-control study. Setting: Laboratory. Participants: Two hundred older individuals volunteered to participate in the study. All individuals completed the Identification of Functional Ankle Instability (IdFAI) to determine CAI status. There were 75 individuals classified as CAI (age = 51.5 ± 7.3 years, height = 175.8 ± 3.7 cm, body mass = 86.5 ± 18.9 kg) and 125 classified as no CAI (age = 53.2 ± 7.3 years, height = 176.2 ± 5.4 cm, body mass = 81.3 ± 17.6 kg). Assessment of risk factors: The independent variable was CAI status. Individuals scoring ≥11 on the IdFAI were classified as having CAI, and those scoring <11 as not having CAI. Main outcome measurements: All participants completed the American Academy of Orthopaedic Surgeons Lower Limb Questionnaire (AAOS) and the Short Form-36 (SF-36v2) on one occasion. Dependent variables were the scores on the AAOS, the eight dimensions of the SF-36v2 (vitality (VT), physical functioning (PF), bodily pain (BP), general health (GH), physical role functioning (RF), emotional role functioning (RE), social role functioning (SF), and mental health (MH)), and two summary scores (physical (PCS) and mental (MCS) components). A MANOVA was used to evaluate differences between the two groups on all dependent variables. A priori alpha was set a p < 0.05. Results: Compared with the individuals without CAI, those with CAI reported decreased function on the AAOS, PF, BP, GH, RP, and PCS (p < 0.05). The largest mean difference was seen in the AAOS (10.02 points). Conclusions: Individuals with CAI reported decreased function and HRQoL compared with individuals without CAI. These findings suggest that HRQoL should be examined during the evaluation and rehabilitation process of individuals with CAI.